Workload Analysis of The Merchant Ship Division Using The Full Time Equivalent Method - Ambikka Ambikka; Reny Nadlifatin (Eduvest - Journal of Universal Studies, 2024)
As a production division in a government-owned shipyard, the Commercial Ship Division has a direct workforce of 28% of PT PAL Indonesia's workforce. The revenue generated annually reaches 46% of the company's total revenue, with an increase in revenue reaching 50% each year. With the large number of direct labor, revenue targets and the complexity of the ship production process, workload analysis needs to be done to measure the workload of direct labor and the number of direct labor needed. Workload analysis is carried out using the Full Time Equivalent (FTE) method, where the FTE Index resulting from the calculation will be grouped into three categories namely underload, normal and overload. From the calculation of the FTE index of direct labor in the Commercial Ship Division, there are 5 people in the underload category, 27 people in the normal category and 134 people in the overload category. From the results of the calculation of direct labor requirements using the Full Time Equivalent method as well as optimization and efficiency of labor, the number of direct labor requirements for the Commercial Ship Division is 315 people.